2021
DOI: 10.33736/jcshd.3808.2021
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude and Its Relationship to Resilience and Academic Performance among University Students

Abstract: This study examines the relationship between gratitude, resilience, and academic performance among students of a public university in Malaysia. One hundred and forty-six samples were obtained through a simple random technique (N=235). The survey employed GQ6 (Gratitude Questionnaire), Brief Resilience Scale (BRS), and self-reported grade-point average (GPA) as its measurement tools. Correlation analysis shows that gratitude has a high positive relationship with resilience and academic performance. Findings fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
1
9
0
2
Order By: Relevance
“…The results verified H2 that gratitude exerted a partially mediating role between parent-child relationships and the academic performance of college students, consistent with the results of previous studies ( Li et al, 2021 ; Obeldobel and Kerns, 2021 ; Zainoodin et al, 2021 ). It suggests that a positive parent–child relationship is an essential context for developing individual gratitude, stimulating positive life orientations in college students and promoting their focus on the good things in life, thus generating positive motivation and ultimately resulting in good academic performance.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results verified H2 that gratitude exerted a partially mediating role between parent-child relationships and the academic performance of college students, consistent with the results of previous studies ( Li et al, 2021 ; Obeldobel and Kerns, 2021 ; Zainoodin et al, 2021 ). It suggests that a positive parent–child relationship is an essential context for developing individual gratitude, stimulating positive life orientations in college students and promoting their focus on the good things in life, thus generating positive motivation and ultimately resulting in good academic performance.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the parent–child relationship is an antecedent variable of psychological capital and significantly and positively impacts the individual psychological capital ( Kwok et al, 2015 ; Chen et al, 2017 ; Nolzen, 2018 ; Carmona-Halty et al, 2020 ; Choi, 2021 ). Recent studies have reported that gratitude and psychological capital allow students to cope positively with their study and life; these are critical for college students ( Du and Chen, 2021 ; Maykrantz et al, 2021 ; Wang et al, 2021 ; Zainoodin et al, 2021 ). Individuals with high gratitude and psychological capital levels have better academic performance ( Sevari and Farzadi, 2018 ; Carmona-Halty et al, 2019 ; Martínez et al, 2019 ; Clarkson, 2020 ; Slåtten et al, 2021 ; Zainoodin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations